FREEDOM AND NECESSITY AS VECTORS OF THE DEVELOPMENT OF GLOBAL SOCIETY: REALITIES AND PROSPECTS - Yarlakabov, Jamshid (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2025)
The question of freedom and necessity in society is a complex and multifaceted socio – philosophical process, which has a special significance in the modern world. In particular today, there is an increasing amount of immorality in society due to the misinterpretation of the concept of freedom. This article will talk about the role of the concepts of freedom and necessity in the development of global society, the realities and prospects of today.